Pengaruh Penyuluhan Terhadap Keikutsertaan Dalam Mengikuti Kelas Ibu Hamil Di Puskesmas Tunas Harapan Rejang Lebong Tahun 2024 - Kristi Fani, Nofela; Aulia Umami, Desi; Hilinti, Yatri (Jurnal Pakar Kesehatan, 2025)
. One of the agendas of the Sustainable Development Goals (SDGs) is to reduce maternal and infant mortality rates. Quality and regular antenatal care during pregnancy determines the health status of both the pregnant mother and the baby. Increasing knowledge and changing the attitudes of mothers regarding their own health and their child's health are important. The Ministry of Health has packaged this into the program of Pregnancy and Toddler Classes. According to data from the Tunas Harapan Rejang Lebong Health Center, the number of pregnant women in 2021 was 218, in 2022 it was 217, and in 2023 it increased to 231. The effect of counseling on the participation of pregnant women in attending pregnancy classes at Tunas Harapan Rejang Lebong Health Center in 2024 was determined. This research uses a pre-experimental design with a one-group pretest-posttest approach. The total sampling technique was used, meaning the entire population was sampled. The sample received treatment in the form of counseling. Thus, the research sample consisted of 31 pregnant women.Univariate results showed that all respondents had never attended pregnancy classes (100%). Almost all pregnant women respondents (87.1%) participated in the pregnancy classes at Tunas Harapan Rejang Lebong Health Center in 2024. Bivariate results found that P-value = 0.000 < 0.05, indicating that there is an effect of counseling on the participation of pregnant women in attending pregnancy classes at Tunas Harapan Rejang Lebong Health Center in 2024. Pregnant women should attend pregnancy classes regularly to better manage their behavior and avoid pregnancy danger signs.